CHALLENGES FACED IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS - Mamatova Muslima Sanjarbek qizi; Jalolova Muqaddasxon (TADQIQOTLAR, 2025)
Abstract:This article explores the main challenges educators encounter when teaching foreign languages to young learners. While early language acquisition offers significant cognitive and linguistic benefits, teachers must also navigate issues such as limited attention spans, lack of motivation, developmental differences, and classroom management. The article reviews current research and offers practical insights into strategies for addressing these difficulties in early language education settings.